DEVELOPMENT AND VALIDATION OF A RP-HPLC METHOD FOR SIMULTANEOUS DETERMINATION OF ARTEMETHER AND LUMEFANTRINE IN TABLET DOSAGE FORM: Pharmaceutical Sciences-Analysis - POPATRAO WAGH, MILIND; ARVIND RANPISE, ANURADHA (International Journal of Life Science and Pharma Research, 2017)
A simple, sensitive, specific, precise and accurate stability indicating reverse phase liquid chromatographic method was developed for simultaneous determination of Artemether and Lumefantrine in bulk drugs and pharmaceutical formulations. The chromatographic analysis was performed by MicrosorbMV100-5 C-18 column (250 x 4.6mm, 5 µm), with mobile phase consisting of buffer and acetonitrile in the ratio of 65:35v/v, orthophosphoric acid used as buffer (pH 3.5), at a flow rate of 1 ml/min and eluents monitored at 254nm. The method was validated for linearity, accuracy, precision, robustness and application for assay as per ICH guidelines. The retention times of Artemether and Lumefantrine were 2.67 and 4.62 min, respectively. The calibration curves of peak area versus concentration, which was linear from 5- 30µg/ml for Artemether and 60-210µg/ml for Lumefantrine, had regression coefficient (r2 ) greater than 0.999 & precise (R.S.D. < 2.0%). The method had the requisite accuracy, precision, and robustness for simultaneous determination of Artemether and Lumefantrine in tablets.